2021
DOI: 10.4196/kjpp.2021.25.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin reduces orofacial nociceptive responses and microglial p38 mitogen-activated protein kinase phosphorylation in trigeminal nucleus caudalis in mouse orofacial formalin model

Abstract: The mammalian target of rapamycin (mTOR) plays a role in various cellular phenomena, including autophagy, cell proliferation, and differentiation. Although recent studies have reported its involvement in nociceptive responses in several pain models, whether mTOR is involved in orofacial pain processing is currently unexplored. This study determined whether rapamycin, an mTOR inhibitor, reduces nociceptive responses and the number of Fos-immunoreactive (Fos-ir) cells in the trigeminal nucleus caudalis (TNC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The sham procedure consisted of exposing the ION, with care taken to avoid stretching the nerve or damaging the epineurium. were selected based on a previous study (Yeo et al, 2021). The final vehicle (VEH) was adjusted to 0.2% DMSO in saline.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The sham procedure consisted of exposing the ION, with care taken to avoid stretching the nerve or damaging the epineurium. were selected based on a previous study (Yeo et al, 2021). The final vehicle (VEH) was adjusted to 0.2% DMSO in saline.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The TNC and TG tissues were scanned using an ECLIPSE 80i (Nikon Corp., Kanagawa, Japan) fluorescent microscope, and individual sections were digitized with 4,096 gray levels using a cooled CCD camera (Cool Snap ES model, Nihon Roper, Tokyo, Japan) connected to a computer-assisted image analysis system (MetaMorph; Universal Imaging, Westchester, PA). As previously described (Yeo et al, 2021), for quantitative analysis in the TNC region, six nonadjacent tissue sections per mouse were randomly selected and analyzed with a computer-assisted image analysis system (MetaMorph version 7.7.2.0). To analyze the p-p38 images, cells that were at least 80% brighter than the average level of each image were counted.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling via the mammalian target of rapamycin, which controls mRNA translation and mediates opioid tolerance and hyperalgesia, is a potential target for improving opioid efficacy and analgesia [4]. In preclinical studies, the antifungal agent rapamycin has been shown to reduce inflammatory and neuropathic pain [5,6]. Other animal studies have found that tetracycline derivatives may attenuate neuropathic pain through the inhibition of EphB1 tyrosine kinase, which is a mediator of neuropathic pain and morphine tolerance, and that the antimicrobial peptide piscidin-1 may possess antinociceptive effects in neuropathic pain models [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain in the orofacial area is commonly observed in humans and markedly reduces the quality of general life by disrupting food intake, face washing, and tooth brushing (Costigan et al, 2009 ). Yeo's colleagues previously proved that an mTOR inhibitor rapamycin suppressed orofacial formalin-induced pain (Yeo et al, 2021 ). Therefore, to elucidate its underlying mechanism, Yeo and Roh explored the effect of rapamycin on the orofacial pain by nerve injury and the changes of mTOR signaling-related proteins, ERK, JNK, p38 MAPK, and glial cells in the trigeminal nucleus caudalis (TNC).…”
mentioning
confidence: 99%